The Theory and Measurement of Expertise-Based Problem Solving in Organizational Teams: Revisiting Demonstrability - Bonner, Bryan L.; Shannahan, Daniel; Bain, Kristin; Coll, Kathryn; Meikle, Nathan L. (Organization Science, 2022)
The current paper revisits and builds upon task demonstrability, which defines the criteria necessary for groups to choose a correct response if any member prefers that response. We identify boundary conditions of the current conceptualization of task demonstrability with respect to its use in understanding modern organizational teams. Specifically, we argue that, in its current form, task demonstrability is not optimally suited to studying ongoing teams in which member expertise varies and teams work to complete complex multifaceted tasks. To address this issue, we provide a revisited perspective on demonstrability. We specify the nomological network of revisited demonstrability and recast each of its criteria in a form that preserves the original intent of the construct, but has broader applicability, particularly to organizational contexts. We then discuss theoretical implications and managerial applications of the construct. Finally, noting that there is no standard assessment tool for demonstrability (original or revisited), we develop and validate a measure to facilitate future research.